2004
DOI: 10.4049/jimmunol.172.8.4902
|View full text |Cite
|
Sign up to set email alerts
|

A Leucine-Rich Repeat Motif of Leishmania Parasite Surface Antigen 2 Binds to Macrophages through the Complement Receptor 3

Abstract: Membrane glycoconjugates on the Leishmania parasites, notably leishmanolysin and lipophosphoglycan, have been implicated in attachment and invasion of host macrophages. However, the function of parasite surface Ag 2 (PSA-2) and membrane proteophosphoglycan (PPG) has not been elucidated. In this study we demonstrate that native and recombinant Leishmania infantum PSA-2, which consists predominantly of 15 leucine-rich repeats (LRR) and a recombinant LRR domain derived from L. major PPG, bind to macrophages. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 31 publications
1
63
0
1
Order By: Relevance
“…Of these, we cannot implicate FcgR for the changes brought about by Leishmania contact, because opsonized parasites were not used by us. The role of CR3 cannot be ruled out completely because L. major surface molecule PSA has been shown to bind with host monocyte CR3 receptor [37]. Signaling through MR has been extensively implicated in the subversion of macrophage proinflammatory responses in another important intracellular infection, M. tuberculosis [38].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, we cannot implicate FcgR for the changes brought about by Leishmania contact, because opsonized parasites were not used by us. The role of CR3 cannot be ruled out completely because L. major surface molecule PSA has been shown to bind with host monocyte CR3 receptor [37]. Signaling through MR has been extensively implicated in the subversion of macrophage proinflammatory responses in another important intracellular infection, M. tuberculosis [38].…”
Section: Discussionmentioning
confidence: 99%
“…parasites with normal mouse serum is not necessary for inhibition (data not shown), suggesting that CR3 ligation is not mediating the interaction. However, MP are able to synthesize complement components (McPhaden and Whaley, 1993) that opsonize parasites even in serum-free conditions (Wozencraft et al, 1986) and parasite components have been suggested to bind CR3 directly (Russell and Wright, 1988;Talamas-Rohana et al, 1990;Kedzierski et al, 2004). Furthermore, the repetitive structure and glycan modifications associated with many Leishmania spp.…”
Section: Discussionmentioning
confidence: 99%
“…Another macrophage cell surface receptor that has acquired multiple, relatively low-affinity ligand binding activities is the CR3 complement receptor, which recognizes a range of ligands, including opsonized bacteria and viruses, Leishmania surface antigens, intracellular adhesion molecule-1, and fibrinogen, and can also mediate macrophage adhesion (117,118).…”
Section: Why So Many Receptors? Why So Many Ligands?mentioning
confidence: 99%